Origin and paragenetic relations of chert nodules in the Florence Limestone, Flint Hills, Kansas - Mallawa Nanayakkaralage Gedara, Minindu (Kansas State University, 2024)
The presence of chert nodules within Florence Limestones in the Flint Hills, Kansas, is partially responsible for its "rolling hills" landscape, as chert is resistant to weathering, holding the topography in this limestone-dominated terrain. It is also an important archeological material, since prehistoric communities used it for tools and trade due to its inherent strength. Despite its ubiquitous presence in the area, the source of silica and paragenetic relations of the minerals in these nodular cherts have not been investigated. This research used a variety of approaches to unravel the source of silica and understand the timing of the formation of the chert nodules. Fieldwork, petrographic analysis, X-Ray Diffraction, and Raman spectroscopy indicated that the Florence Limestone underwent multiphase silicification, starting with the precipitation of opaline silica along burrow pathways during eodiagenesis, followed by other silica polymorphs (microcrystalline quartz and chalcedony) precipitated at later stages. The identification of moganite, along with the presence of halite molds and gypsum nodules in the succession, indicates that evaporite conditions contributed to silica supersaturation. Oxygen isotopes reveal that samples underwent paleotemperatures around 35⁰ C – 40⁰ C minimum, corroborating the interpretation of burial under eodiagenetic conditions. The silica-germanium ratios of 0.4 x 10⁶ - 1.25 x 10⁶, obtained for the different silica phases (opaline, chert, chalcedony, and megaquartz), are compatible with a biogenic origin for the silicifying solutions, which is in agreement with the presence of siliceous organisms (sponge spicules and radiolarians) in the limestones. Therefore, the silica nodules were formed shortly after deposition by the percolation of silica-rich solutions along burrow networks, resulting in the precipitation of opaline silica, followed by chert, chalcedony and finally megaquartz. Silicifying solutions were derived from the dissolution of siliceous organisms, augmented by highly evaporite conditions.
Keywords: Silica; Diagenesis; Chert; Kansas; Nodules